2018
DOI: 10.3389/fpls.2018.00327
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hydrogen Peroxide in Mediating the Mechanical Wounding-Induced Freezing Tolerance in Wheat

Abstract: Systemic wound response (SWR), a well-characterized systemic signaling response, plays crucial roles in plant defense responses. Progress in understanding of the SWR in abiotic stress has also been aided by the researchers. However, the function of SWR in freezing stress remains elusive. In this study, we showed that local mild mechanical wounding enhanced freezing tolerance in newly occurred systemic leaves of wheat plants (Triticum aestivum L.). Wounding significantly increased the maximal photochemical effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 99 publications
1
11
0
Order By: Relevance
“…However, the role that GLVs play in plant abiotic stress remains an open question. Previous studies, including our research, documented the importance of wounding- or herbivore-induced phytohormones, such as ethylene (ETH) and jasmonic acid (JA), and signaling molecules, such as hydrogen peroxide (H 2 O 2 ) and nitric oxide (NO), in response to plant abiotic stress (León et al, 2001; Schilmiller and Howe, 2005; Chauvin et al, 2012; Ahmad et al, 2016; Si et al, 2017, 2018); thus, GLVs might also be a crucial molecule in plant abiotic stress.…”
Section: Introductionmentioning
confidence: 71%
“…However, the role that GLVs play in plant abiotic stress remains an open question. Previous studies, including our research, documented the importance of wounding- or herbivore-induced phytohormones, such as ethylene (ETH) and jasmonic acid (JA), and signaling molecules, such as hydrogen peroxide (H 2 O 2 ) and nitric oxide (NO), in response to plant abiotic stress (León et al, 2001; Schilmiller and Howe, 2005; Chauvin et al, 2012; Ahmad et al, 2016; Si et al, 2017, 2018); thus, GLVs might also be a crucial molecule in plant abiotic stress.…”
Section: Introductionmentioning
confidence: 71%
“…These observations differ from our previous results where non‐stomatal limitations occurred (Si et al . ). This could be because of the different growth environments of the wheat plants between hydroponic culture and our field experiment.…”
Section: Discussionmentioning
confidence: 97%
“…In our previous study, we clearly demonstrated that local mechanical wounding can enhance freezing tolerance of the non‐wounded systemic leaves and the latest fully expanded leaves in wheat (Si et al . , ). However, whether this SWR‐triggered freezing resistance could be applied under field conditions remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several decades, the systemic wounding response (SWR) has become a promising approach in combating plant abiotic stress (Schilmiller and Howe ). Previous studies, including ours, have provided strong evidence that mechanical wounding could enhance abiotic stress tolerance in various plant species (Capiati et al , Si et al , Si et al , Si et al ). Several studies indicate that H 2 O 2 , JA and salicylic acid (SA) are integral systemic signals in plant salt stress (Miller et al , Miller et al , Choudhury et al ); however, the mechanisms governing SWR have not been elucidated in detail.…”
Section: Introductionmentioning
confidence: 50%